Application of case-based learning in psychology teaching: a meta-analysis - Wu, Fanghui; Wang, Tao; Yin, Danxu; Xu, Xiaoxiao; Jin, Cancan; Mu, Nan; Tan, Qingrong (BMC medical education, 2023)
Background Case-based learning (CBL) has been found to be effective for many subjects, but there is currently a lack of evidence regarding its utility in psychology education. The present study investigated whether CBL pedagogy can improve students' academic performance in psychology courses compared to the traditional teaching methods. Methods A systematic review and meta-analysis were conducted to investigate the effectiveness of CBL in psychology teaching. Databases including PubMed, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), the VIP database, and Wanfang data were searched to find eligible randomized controlled trials. Pooled effect estimates were calculated using Hedges' g under the random effects model, and a subgroup analysis was carried to investigate the heterogeneity among studies. Results Fifteen studies with 2172 participants, 1086 in the CBL group and 1086 in the traditional lecture-based teaching group, were included in the meta-analysis. Students in the CBL group scored significantly higher on exams than those in the lecture-based group [Hedges' g = 0.68, 95%CI (0.49, 0.88), p < 0.00]. Relatively high heterogeneity was noted among the included studies. Publication bias was examined by the funnel plot and Egger's test, but did not significantly influence the stability of the results. A subsequent evaluation using the trim-and-fill method confirmed that no single study was skewing the overall results. A qualitative review of the included studies suggested that most students in the CBL group were satisfied with the CBL teaching mode. Conclusions This meta-analysis indicated that the CBL pedagogy could be effective in psychology education, and might help increase students' academic scores, while encouraging a more engaging and cooperative learning environment. At present, the application of CBL in psychology education is in its initial stage. Problems related to the curriculum itself, research methodology, and challenges faced by both teachers and learners have confined its practice. Fully tapping into the strengths of CBL in psychology teaching will require additional work and advancing research. Keywords: Case-based learning, Traditional lecture, Psychology, Education, Meta-analysis